BARRIERS IN CLASSROOM MANAGEMENT AND COURSE CLIMATE - Bekkulova Hojar Zayniddinovna; Akramova Kamola Akramovna; Shomurodova Shahlo Jahonovna; Nazarova Nurjahon Bahodirovna (International Engineering Journal For Research & Development, 2020)
Teachers are responsible for delivering classroom‐management plans and behavior support plans; however, many struggle to implement them consistently. Low levels of treatment integrity may be the result of various implementation barriers. No study has been conducted to examine teachers’ experience of these barriers within the context of specific interventions.